2011
DOI: 10.3174/ajnr.a2567
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Misinterpretations on Pediatric Neuroimaging Studies: Classification, Imaging Analysis, and Outcome Assessment

Abstract: BACKGROUND AND PURPOSE:The scope of trainee misinterpretations on pediatric neuroimaging studies has been incompletely assessed. Our aim was to evaluate the frequency of trainee misinterpretations on neuroimaging exams in children, describe a useful classification system, and assess related patient management or outcome changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…There was no difference between resident major discrepancy rates by type of report, general pediatric radiology CT and pediatric neuroradiology CT, which coincides with similar reports (810). This suggests that the skillsets needed to interpret these two types of CT scans do not differ.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was no difference between resident major discrepancy rates by type of report, general pediatric radiology CT and pediatric neuroradiology CT, which coincides with similar reports (810). This suggests that the skillsets needed to interpret these two types of CT scans do not differ.…”
Section: Discussionsupporting
confidence: 89%
“…Two studies demonstrated a significant discrepancy rate of 2% and 2.5%, and another study demonstrated a similar finding of 1.7% (4,8,9). A study that examined discrepancy rates on pediatric neuroimaging studies demonstrated a major discrepancy rate of 0.17% on pediatric neuroimaging studies and found that most discrepancies occurred on CT examinations (10).…”
Section: Introductionmentioning
confidence: 99%
“…This can be difficult in patients with multiple fractures in which it is important to distinguish those fractures that are surgically relevant. In a paper by Guimaraes, the most common trainee misinterpretation of facial CT was facial fractures, highlighting further the importance of a systematic method for maxillofacial CT analysis …”
Section: Introductionmentioning
confidence: 99%